Assessment of the quality of life in metastatic colorectal cancer patients with KRAS gene mutant: a case-control study - Fahmideh Bagrezaei; Bahram Pourghassem Gargari; Reza Eghdam Zamiri; Abdolrasoul Safaiyan; Mohammad Alizadeh (BMC Cancer)
Abstract Background The mutation of the KRAS (Kirsten rat sarcoma virus) gene is a prevalent genetic alteration in metastatic colorectal cancer (mCRC). According to previous research, this mutation significantly affects clinical outcomes and quality of life (QOL). This research investigated the association between KRAS mutant status and various aspects of QOL in mCRC patients. Methods This case-control study involved 90 admitted patients with mCRC. The patients were either mCRC with positive KRAS mutants (case group) or those without the mutation (control group). The KRAS mutation status of each patient was determined using standard molecular testing. The QOL was evaluated through validated questionnaires from the European Organization for Research and Treatment of Cancer (EORTC), including QLQ-C30 and the QLQ-CR29 questionnaire for colorectal cancer patients. Differences in QOL between the groups and the association of QOL with the odds of KRAS mutation were analyzed using appropriate statistical tests. Results Patients in the wild-type KRAS group had significantly higher scores on the global health status (GHS) of the QLQ-C30 scale compared to those with a KRAS mutation [(64.26 ± 4.63 vs. 49.63 ± 4, crude; p = 0.019, adjusted; p = 0.024). The mean score of the social functioning scale of the KRAS mutation group was significantly higher than the wild-type [(40 ± 5.84 vs. 24.81 ± 4.39, crude; p = 0.040, adjusted; p = 0.021)]. Based on the QLQ-CR29 questionnaire, average QOL scores were suboptimal for both groups but insignificant. Further, both crude and adjusted analyses showed that KRAS mutation odds were significantly linked to improved social functioning [(crude; OR = 1.013; P = 0.044), (adjusted; OR = 1.017; P = 0.019)] and negatively associated with GHS [(crude; OR = 0.983; P = 0.022), (adjusted; OR = 0.982; P = 0.022)]. Conclusion The study revealed a low QOL in mCRC, a notable difference in social functioning, and the GHS among patients with and without mutations. Further research is needed to develop targeted interventions to enhance QOL in patients with KRAS mutation.